CORDIERITE AS A SENSOR OF FLUID CONDITIONS IN HIGH-GRADE METAMORPHISM AND CRUSTAL ANATEXIS - Harley S.L.; Thompson P.; Hensen B.J.; Buick I.S. (My University, 2002)
Cordierite H2O and CO2 volatile saturation surfaces derived from recent experimental studies are presented for P–T conditions relevant to high-grade metamorphism and used to evaluate fluid conditions attending partial melting and granulite formation. The volatile saturation surfaces and saturation isopleths for both H2O and CO2 in cordierite are strongly pressure dependent. In contrast, the uptake of H2O by cordierite in equilibrium with melts formed through biotite dehydration melting, controlled by the distribution of H2O between granitic melt and cordierite, Dw[Dw = wt% H2O (melt)/wt% H2O(Crd)], is mainly temperature dependent. Dw = 2.5–6.0 for the H2O contents (0.4–1.6 wt percentage) typical of cordierite formed through biotite dehydration melting at 3–7 kbar and 725–900 °C. This range in Dw causes a 15–30% relative decrease in the total wt% of melt produced from pelites. Cordierite in S-type granites are H2O-rich (1.3–1.9 wt%) and close to or saturated in total volatiles, signifying equilibration with crystallizing melts that achieved saturation in H2O. In contrast, the lower H2O contents (0.6–1.2 wt percentage) preserved in cordierite from many granulite and contact migmatite terranes are consistent with fluid-absent conditions during anatexis. In several cases, including the Cooma migmatites and Broken Hill granulites, the cordierite volatile compositions yield aH2O values (0.15–0.4) and melt H2O contents (2.2–4.4 wt%) compatible with model dehydration melting reactions. In contrast, H2O leakage is indicated for cordierite from Prydz Bay, Antarctica that preserve H2O contents (0.5–0.3 wt%) which are significantly less than those required (1.0–0.8 wt%) for equilibrium with melt at conditions of 6 kbar and 860 °C. The CO2 contents of cordierite in migmatites range from negligible (< 0.1 wt%) to high (0.5–1.0 wt%), and bear no simple relationship to preserved cordierite H2O contents and aH2O. In most cases the cordierite volatile contents yield total calculated fluid activities (aH2O + aCO2) that are significantly less than those required for fluid saturation at the P–T conditions of their formation. Whether this reflects fluid absence, dilution of H2O and CO2 by other components, or leakage of H2O from cordierite is an issue that must be evaluated on a case-by-case basis.